MODEL SKEDUL MIGRASI DAN APLIKASINYA DALAM PROYEKSI PENDUDUK MULTIREGIONAL - MUSLIMAH, M.; SUMARNO, H.; KUSNANTO, A. (School of Data Science, Mathematics and Informatics, IPB University, 2009)
Migration is one of demographic component beside fertility and mortality. The objective of thesis is to find model migration schedules and its application to multiregional population projection. Rogers et al. (1978) proposed one model migration schedules consist of 11 parameters. As the comparisson to that model this paper proposed another model used polinomial function. By divided Indonesia into two regions, Java-Bali and outer JavaBali, it would be found model migration schedules. The model be implemented to multiregional population projection based on SUPAS 2005 data. The result showed that the population growth continu to decreased and will reach -0,00066 in stable condition.